UJI MUTU BENIH BUNGA MATAHARI PADA PERBEDAAN METODE PENGERINGAN DAN APLIKASI FUNGISIDA - Ni Kadek Ema Sustia Dewi; Luh Putu Yuni Widyastuti; Ni Wayan Purnami Rusadi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
This research aims to examine the viability of sunflower seeds against different drying methods and fungicide applications. This experiment consisted of two factors with a Completely Randomized Design (CRD). The first factor is the drying method, namely drying in the sun (control) with an average of 31°C for six days, cake oven and costume oven with temperatures ranging from 36.5-37.5°C for four days. The second factor is the application of fungicides, namely without fungicides and fungicides. Seed quality testing is carried out using the UKDdP method. The experiment consisted of 6 treatment combinations which were repeated three times so that there were 18 experimental units. Each experimental unit used 25 seeds. The results showed that the lowest water content was 6.25% from sun drying and the highest germination rate was 73.33%. The sun drying method and the use of fungicides can produce the lowest water content, and have the highest values ​​in the percentage of germination, vigor index, maximum growth potential, normal dry weight of sprouts, as well as the use of fungicides. It is necessary to test the temperature and drying period using a cake and custom oven to get the right time to maintain seed viability.